Introducing a common taxonomy to support learning from failure in conservation. Issue 1 (15th December 2022) - Dickson, Iain; Butchart, Stuart H. M.; Catalano, Allison; Gibbons, David; Jones, Julia P. G.; Lee‐Brooks, Katie; Oldfield, Thomasina; Noble, David; Paterson, Stuart; Roy, Sugoto; Semelin, Julien; Tinsley‐Marshall, Paul; et al.
Abstract: Although some sectors have made significant progress in learning from failure, there is currently limited consensus on how a similar transition could best be achieved in conservation and what is required to facilitate this. One of the key enabling conditions for other sectors is a widely accepted and standardized classification system for identifying and analyzing root causes of failure. We devised a comprehensive taxonomy of root causes of failure affecting conservation projects. To develop this, we solicited examples of real‐life conservation efforts that were deemed to have failed in some way, identified their underlying root causes of failure, and used these to develop a generic, 3‐tier taxonomy of the ways in which projects fail, at the top of which are 6 overarching cause categories that are further divided into midlevel cause categories and specific root causes. We tested the taxonomy by asking conservation practitioners to use it to classify the causes of failure for conservation efforts they had been involved in. No significant gaps or redundancies were identified during this testing phase. We then analyzed the frequency that particular root causes were encountered by projects within this test sample, which suggested that some root causes were more likely to be encountered than others and that a small number of root causes were more likely to be encountered by projects implementing particular types of conservation action. Our taxonomy could be used to improve identification, analysis, and subsequent learning from failed conservation efforts, address some of the barriers that currently limit the ability of conservation practitioners to learn from failure, and contribute to establishing an effective culture of learning from failure within conservation. Abstract : Introducción de una taxonomía común como apoyo al aprendizaje a partir del fracaso en la conservación Resumen: Mientras que algunos sectores han progresado significativamente en el aprendizaje a partir del fracaso, actualmente hay un consenso limitado sobre cómo podría lograrse una transición similar en la conservación y qué se requiere para facilitarla. Una de las condiciones habilitantes más importantes en otros sectores es un sistema de clasificación estandarizado y aceptado por la mayoría para la identificación y análisis de las causas fundamentales del fracaso. Diseñamos una taxonomía completa de las causas fundamentales del fracaso que afecta a los proyectos de conservación. Para desarrollarla, solicitamos ejemplos de esfuerzos de conservación reales que de alguna manera se consideraron como fracasos, identificamos las causas fundamentales no aparentes de su fracaso y luego las usamos para desarrollar una taxonomía genérica de tres niveles de las maneras en las que fracasan los proyectos, en cuyo nivel superior están seis categorías de causas generales que después se dividen en categorías de nivel medio de categorías de causas y causas fundamentales específicas. Pusimos a prueba la taxonomía al pedirle a los practicantes de la conservación que la usaran para clasificar las causas del fracaso de los esfuerzos de conservación en los que han participado. No identificamos vacíos o redundancias importantes durante esta fase de prueba. Después, analizamos la frecuencia con la que los proyectos de esta muestra se enfrentaron a causas fundamentales particulares, lo que sugirió que algunas causas fundamentales tienen mayor probabilidad de ocurrir y que un número reducido de causas fundamentales tiene mayor probabilidad de ocurrir en proyectos que implementan ciertos tipos de acciones de conservación. Nuestra taxonomía podría usarse para mejorar el análisis, identificación y aprendizaje subsecuente a partir del fracaso de los esfuerzos de conservación; tratar algunas de las barreras que en la actualidad limitan a los practicantes de la conservación a aprender del fracaso; y contribuir al establecimiento de una cultura efectiva del aprendizaje a partir del fracaso dentro de la conservación. 【摘要】: 虽然一些部门能够很好地从失败中吸取教训, 但目前对于如何在保护中最好地实现类似的转变及其必需条件的共识仍十分有限。其他部门的关键赋能条件之一是有一个广泛被接受和标准化的分类系统来识别和分析失败的根本原因。本研究设计了一个影响保护项目失败的根本原因的综合分类法。为了建立这一套分类法, 我们收集了现实世界中被认为在某些方面失败了的保护工作的案例, 确定了其失败的根本原因, 并利用这些案例制定了一个通用的项目失败方式三层分类法, 其顶端是六个总体原因类别, 并进一步分为中层原因类别和具体根源。我们要求保护实践者使用该分类法对他们所参与的保护工作的失败原因进行分类, 以对该分类法进行测试。在测试阶段没有发现明显的空缺或冗余。接下来, 我们分析了测试样本项目遇到特定失败根源的频率, 结果表明一些根源更为常见, 少数根源更有可能在实施特定类型保护行动的项目中出现。我们的分类法可用于改进对失败保护工作的识别、分析及随后的教训学习, 解决目前限制保护实践者从失败中学习的能力的一些障碍, 并有助于在保护中建立有效的从失败中学习的文化。【翻译: 胡怡思; 审校: 聂永刚】